Caffeine removal by Gliricidia sepium biochar: Influence of pyrolysis temperature and physicochemical properties - Keerthanan, S; Rajapaksha, Suranga M; Trakal, Lukáš; Vithanage, Meththika (Environmental research. Section A, 2020)
The present study aimed to envisage the effect of physicochemical properties on the performance of Gliricidia sepium biochar (GBC) pyrolyzed at 300, 500, and 700 °C in the removal caffeine (CFN); a pharmaceutical and personal care product, from water. The physicochemical properties of GBC were characterized by proximate and ultimate analysis, BET, SEM, FTIR, and Raman spectroscopy. The adsorption batch experiment was carried out at various pH values (pH 3-10), mixing times (up to 24 h), and initial CFN concentration (10-500 mg/L). The FTIR analysis revealed the loss of polar functional groups on the surface of GBC derived at high temperatures. The red-shifted and blue-shifted Raman peaks indicate the condensation of small molecules on GBC. The GBC derived at 700 °C demonstrated high CFN adsorption capacity (16.26 mg/g) due to its high surface area and aromaticity. The highest adsorption of CFN was occurred at acidic pH range from 3.5 to 4.5 due to the existence of non-specific attraction between CFN and GBC. The kinetics and isotherm experimental data were fitted with Elovich and fractional power kinetic regression, Freundlich, and Temkin isotherm models, which suggested the adsorption of CFN on the GBC by mixed mechanisms; physisorption and chemisorption including π-π interactions, hydrogen bonding, n-π interactions, electrostatic attraction, and electron donor-acceptor attraction. Moreover, both surface area and aromaticity index have demonstrated a high positive correlation for CFN adsorption, signifying the importance of controlling physicochemical properties based on the end-user purpose of biochar.
Keywords: chemické látky znečišťující vodu; pyrolýza; koncentrace vodíkových iontů; Charcoal; Kinetics; Water Pollutants, Chemical; adsorpce; kofein; teplota; Hydrogen-Ion Concentration; dřevěné a živočišné uhlí; Pyrolysis; Caffeine; kinetika; Adsorption; Temperature